Cost-Effective Decontamination of Conventional Laboratory Animal Rooms Using Hydrogen Peroxide Aerosols (Journal of Laboratory Animal Science, 2024)
Conventional animal facilities lack HVAC systems with HEPA filters and therefore pose great hurdles in maintaining  the pathogen-free status of macro-environment of the animal rooms. Even in places where HVAC has no HEPA filters,  maintaining clean air in the animal room is a challenge. Production of healthy animals for biomedical research is a key  objective of any laboratory animal facility. There are several factors which can contribute to achieve this goal, and macro enviornment is one of them. Decontamination of animal rooms eliminates the pathogens from the room. Chemical liquids  and vapours are mainly used as decontaminating agents. Vaporised Hydrogen Peroxide (VHP) technology is being widely  used for this purpose. For VHP technology, motorised equimpents are required which are very expensive. Small animal  facilities can not afford to buy expensive VHP equipments. Therefore, the present study was planned to find out cost  effective alternative for expensive equipments. Fine mist of working solution Huwa-San- TR50 was sprayed over the  walls using a domestic Vacuum Cleaner. Effectnivness of decontamination procedure was conducted by microbiological  examination of air and surface monitoring with swab methods after 15 mins. of contact time. Our results suggested that after  decontamination, there was significant reduction in microbiological load from animal rooms. Hence, alternatively, facilities  with tight annual budget can use this technique to limit the microbiological load in animal facilities in cost effective manner.
Keywords: laboratory animals; Efficiency Particulate